Aggressive Skull Base Metastasis from Uveal Melanoma: A Clinicopathologic Study. Issue 5 (September 2014) - Yonekawa, Yoshihiro; Kim, Ivana K.; Gragoudas, Evangelos S.; Njauw, Ching-Ni J.; Tsao, Hensin; Jakobiec, Frederick A.; Stacy, Rebecca C.
Purpose: We present the clinical, pathologic, and genetic findings of the first reported case of choroidal melanoma that developed a late recurrence and aggressive metastasis to the skull base without evidence of hepatic involvement. Methods: Retrospective chart review and clinicopathologic correlation of ocular and brain tissue, including sequencing of BAP1 for mutations. Results: A 55-year-old woman was diagnosed with choroidal melanoma and treated with proton radiotherapy. Six years later, she developed a rapidly growing local recurrence involving the ciliary body and iris. Upon enucleation, histopathology revealed an iris and ciliary body epithelioid melanoma that was contiguous with the previously treated, regressed spindle cell choroidal melanoma. Imaging was initially negative for brain involvement. Two months later, she developed cranial neuropathies and was found to have a large skull base lesion that required surgical debulking for pain palliation. Histopathology confirmed the lesion to be metastatic melanoma. Both ocular and brain tumor specimens were wild-type for BAP1. Throughout her course, she developed no hepatic metastases. Conclusions: Uveal melanoma may metastasize to the skull base. The present case was characterized by delayed onset and unusual aggressiveness of the metastatic disease, and lack of BAP1 mutation. The unusual course highlights a unique phenotype that may reflect an alternate molecular mechanism for metastatic disease.